People and sites as community resources for preventing and managing chronic health conditions: A conceptual analysis. - Prachee Agrawal; Seye Abimbola (Public Library of Science (PLoS), 2024)
The prevention and management of chronic non-communicable diseases (NCDs) require community-based efforts-especially as their burden grows, and recognition of the need for engaging diverse stakeholders in care grows. The aim of this conceptual analysis was to categorise existing community resources (people and sites) used to support such efforts, the mechanisms by which they work, and the conditions that constrain their effectiveness. We developed an initial framework for categorising community resources. We then used a sample of the literature- 24 studies from 12 countries-to refine and enrich the framework. We identified seven categories of sites ('where': House, Meeting place, Community health centre, Primary health care centre, Mobile clinic, Pharmacy, and Hospital) and ten categories of people ('who': Community Health Worker, Nurse/Midwife, Health educator, Physician, Primary Health Care Worker, Peer Group, Navigator, Pharmacist, Cultural Advisor, Family caregiver). We identified eight mechanisms through which those resources improve NCD prevention and management: Context specific engagement, Personalised and integrated care, Community health worker led knowledge dissemination, Social support through family and/or friends, Extending the reach of the health system, Social support through peer groups, Task shifting, and Training of health workforce. We identified two broad categories of constraints on these mechanisms: (i) health system barriers such as inadequate workforce, training, coordination and engagement; and (ii) socio-economic, political, and cultural barriers to care. The conceptual categories (of people and sites as resources, the mechanisms through which they work and the contextual constraints on their effectiveness) identified in this analysis may be useful in further analysing current approaches in NCD efforts using community resources, in informing the development of community-based efforts, and in exploring the commonalities and transferable insights between different locations or settings around the world and between different efforts to prevent and manage NCDs within communities.